Defining Quantitative Targets for Topsoil Organic Carbon Stock Increase in European Croplands: Case Studies With Exogenous Organic Matter Inputs - Bruni, Elisa; Guenet, Bertrand; Clivot, Hugues; Kätterer, Thomas; Martin, Manuel; Virto, Iñigo; Chenu, Claire (Frontiers in Environmental Science, 2022)
The Mission Board for Soil Health and Food proposed a series of quantitative targets for European soils to become healthier. Among them, current soil organic carbon (SOC) concentration losses in croplands (0.5% yr-1 on average at 20 cm depth) should be reversed to an increase of 0.1-0.4% yr-1 by 2030. Quantitative targets are used by policy makers to incentivize the implementation of agricultural practices that increase SOC stocks. However, there are different approaches to calculate them. In this paper, we analyzed the effect of exogenous organic matter (EOM) inputs on the evolution of SOC stocks, with a particular focus on the new European targets and the different approaches to calculate them. First, we illustrated through two case-study experiments the different targets set when SOC stock increase is calculated considering as reference: 1) the SOC stock level at the onset of the experiment and 2) the SOC stock trend in a baseline, i.e. a control treatment without EOM addition. Then, we used 11 LTEs with EOM addition in European croplands to estimate the amount of C input needed to reach the 0.1% and 0.4% SOC stock increase targets proposed by the Mission Board for Soil Health and Food, calculated with two different approaches. We found that, to reach a 0.1% and 0.4% increase target relative to the onset of the experiment, 2.51 and 2.71 Mg C ha-1 yr-1 of additional C input were necessary, respectively. Reaching a 0.1% and 0.4% increase target relative to the baseline required 1.38 and 1.65 Mg C ha-1 yr-1 of additional input, respectively. Depending on the calculation method used, the estimated amounts of additional C input required to reach each quantitative target were significantly different from each other. Furthermore, the quality of C input as represented by the C retention rate of the additional organic material (EOM and crop residue), had a significant effect on the variation of SOC stocks. Our work highlights the necessity to take into consideration the additional C input required to increase SOC stocks, especially for soils with decreasing SOC stocks, when the target is set independently of the baseline.